Bluetooth Security: A Comprehensive Guide to Protecting Your Wireless Devices - Shanu Sahadevan Mary (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the evolving landscape of Bluetooth security, addressing critical aspects of wireless device protection in an increasingly connected world. The article examines fundamental security threats, including bluejacking, bluesnarfing, bluebugging, and spoofing, while providing detailed analyses of their impact on device security. The article delves into effective device management strategies, emphasizing the importance of visibility settings, pairing protocols, and discovery controls. It presents an in-depth evaluation of protection strategies, incorporating multi-layered security approaches, authentication methods, and software maintenance practices. The article extends to modern monitoring and prevention techniques, highlighting the role of artificial intelligence and machine learning in threat detection. The article also outlines implementation guidelines for organizations and users, focusing on daily security practices, risk mitigation techniques, and user awareness protocols. Additionally, it provides valuable insights into the future of Bluetooth security, discussing emerging threats, quantum computing challenges, and the delicate balance between security measures and usability.